Correction: An exchange coupled meso–meso linked vanadyl porphyrin dimer for quantum information processing. Issue 1 (30th November 2022) - Ranieri, Davide; Santanni, Fabio; Privitera, Alberto; Albino, Andrea; Salvadori, Enrico; Chiesa, Mario; Totti, Federico; Sorace, Lorenzo; Sessoli, Roberta
Abstract : Correction for 'An exchange coupled meso – meso linked vanadyl porphyrin dimer for quantum information processing' by Davide Ranieri et al., Chem. Sci., 2022, ; https://doi.org/10.1039/d2sc04969d .